Efficient Biodegradation of Patulin by Aspergillus niger FS10 and Metabolic Response of Degrading Strain - Yang Yang; Jian Ji; Shang Wu; Yongli Ye; Lina Sheng; Yinzhi Zhang; Xiulan Sun (Foods, 2023)
Patulin, a mycotoxin commonly found in fruits and derived products, causes serious health problems for humans and animals worldwide. Several microbial strains have been observed to possess the ability to effectively remove patulin. However, these methods are presently associated with disadvantages such as low degradation efficiency and an unclear biodegradation mechanism. In the current study, the characteristics of patulin degradation via Aspergillus niger FS10 were evaluated, and the mechanisms involved were analyzed using metabolomics technologies. The results showed that the suspension of A. niger FS10 could degrade 94.72% of patulin within 36 h. The moment concentration pf patulin was 0.116 μg/mL, and the detection limit value was 0.01 μg/mL. In addition, the patulin content was reduced to levels below the detection limit within 48 h. A. niger FS10 mainly degrades patulin by producing intracellular enzymes, which can convert patulin into ascladiol. This degradation method can effectively reduce the damage caused by patulin to HepG2 cells. In addition, the patulin treatment significantly affects the pentose phosphate pathway and the glutathione pathway. These two metabolic pathways are speculated to be closely related to patulin degradation via A. niger FS10. The incubation of A. niger FS10 with patulin-contaminated apple pomace can not only eliminate patulin but also increase the utilization of apple pomace. Therefore, our research results provide a new method for addressing patulin contamination in the food and feed industries.